2014
DOI: 10.3141/2435-07
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of Hybrid Main-Line Toll Plazas

Abstract: Traditional main-line toll plazas on expressways may have both safety and operational challenges. Although many studies have demonstrated the operational and environmental impacts of conversion from traditional toll plazas to a barrier-free system (open road tolling), research that quantifies the safety benefits of new tolling systems is lacking. This study evaluated the safety effectiveness of the conversion from a traditional main-line toll plaza design to a hybrid main-line toll plaza (HMTP) system. An HMTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the United States, there are currently many tolled road facilities; these facilities vary in type, size, ownership, and tolling systems deployed (Abuzwidah et al, 2014). Some of these facilities are private along with those owned and operated by various public agencies around the States (Abuzwidah, 2011) (Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, there are currently many tolled road facilities; these facilities vary in type, size, ownership, and tolling systems deployed (Abuzwidah et al, 2014). Some of these facilities are private along with those owned and operated by various public agencies around the States (Abuzwidah, 2011) (Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Even though toll roads offer high mobility benefits, traditional toll facilities may pose high traffic safety risk (Abuzwidah et al, 2014). The literature also showed that different toll collection systems have been adopted by different toll agencies around the world (Mohamed et al, 2000) (Schaufler, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The sudden increase in the number of crashes that has occurred in toll plazas that operate multiple toll lane configurations has generated the need to study driving behavior (6,7). One of the research tools that can be used for toll plaza safety and human factors studies is driving simulators.…”
mentioning
confidence: 99%
“…If no actions are taken to address fatal crashes, road traffic fatalities have been predicted to rise to more than 1.9 million deaths per year by 2020 (9). Driver confusion at toll plazas, difficult merging scenarios, and the resulting unexpected driver behaviors have caused an increment in certain crash patterns and other safety problems at toll plazas with electronic tolling facilities (10)(11)(12).…”
mentioning
confidence: 99%